Targeting Long Non-Coding RNA TTN-AS1 Suppresses Bladder Cancer Progression - Xiao, Huiyuan; Huang, Wen; Li, Yanlei; Zhang, Rongxin; Yang, Long (Frontiers in Genetics, 2021)
Abstract Backgroud: To explore the biological and clinical effects of titin-antisense RNA1(TTN-AS1) in bladder cancer (BLCA), and the association between TTN-AS1 and Activating transcription factor 2 (ATF2) in BLCA. Methods: Kaplan-Meier method was performed to analyze the association between the expression of TTN-AS1 and prognosis of BLCA patients from TCGA dataset and our institution. Quantitative real-time PCR (RT-PCR) was conducted to explore the expression of TTN-AS1 between the patients underwent TURBT and Re-TURBT. MTT assay, Colony formation assay and tumor formation assay was conducted to evaluate the effect of TTN-AS1 on the ability of proliferation in BLCA cell lines. Transwell assay was performed to evaluate the effect of TTN-AS1 on the ability of invasion in BLCA cell lines. Bioinfomatics and Immunohistochemical (IHC) staining was used to relationship between TTN-AS1 and ATF2. Results: The higher expression of TTN-AS1 was related with poorer disease free survival (DFS) in patients with BLCA. And the expression of TTN-AS1 was higher in BLCA patients who underwent Re-TURBT compared BLCA patients who underwent TURBT. Knocking down TTN-AS1 was resulted in inhibiting the ability of proliferation and invasion of bladder cancer cells.The ATF2 may serves as a downstream target of TTN-AS1 in bladder cancer, and the high expression of ATF2 was also related with adverse disease-free survival. Conclusion: Our study reveal that TTN-AS1 which served as an oncogene by activating ATF2 in BLCA. The findings suggested that TTN-AS1 may acts as a novel therapeutic target for patients with BLCA.